Ibn ḥazm's Evangelienkritik : Eine methodische Untersuchung - Behloul, Samuel-Martin (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
The book presents a first attempt to investigate the criticism of the Gospels, hardly considered within the previous research work of the Islamic scholar Ibn ḥazm (d. 1064) referring to its methodological and socio-cultural background. After analysing the hardly accounted, however for the understanding of Ibn ḥazm's thought essential commentary about Aristoteles' logic, the raised reproaches by Ibn ḥazm against the Christians are discussed. The topics include falsification of the Gospels, the irrationality of their contents and of the whole Christian religion. In conclusion the question of the main purpose of its anti-Christian polemic arises in the light of the background of the special socio-political situation in Arabic Andalusia. It's a book written in a general way of understanding offering an interesting and new insight into the history of Islamic/Christian polemics.